الذكاء الروحي والدعم الاجتماعي المدرك كمنبئات بنمو ما بعد الصدمة - زروالي, وسيلة (جامعة الوادي - University of Eloued, 2020)
هدفت هذه الدراسة إلى تعرف مستوى كل من الذكاء الروحي والدعم الاجتماعي المدرك، ونمو ما بعد الصدمة لدى عينة من مرضى السرطان، وإلى الكشف عن علاقة نمو ما بعد الصدمة بكل من الذكاء الروحي والدعم الاجتماعي المدرك. أجريت هذه الدراسة على عينة قوامها (53) مريضا ومريضة من مرضى السرطان اختيروا قصديا من مستشفى محمد بوضياف بمدينة أم البواقي. استعملت الباحثة مقياس الذكاء الروحي من اعدادها، مقياس الدعم الاجتماعي المدرك من إعداد طشطوش (2015)، مقياس نمو ما بعد الصدمة من إعداد كعبر (2017). أسفرت المعالجة الإحصائية للمعطيات على أن أفراد العينة من مرضى السرطان يمتلكون مستويات عالية من الذكاء الروحي، والدعم الاجتماعي المدرك، ونمو ما بعد الصدمة، كما أظهرت نتائج الدراسة وجود علاقة ارتباطية موجبة وقوية دالة إحصائيا عند مستوى دلالة (0.01) بين نمو ما بعد الصدمة وكل من الذكاء الروحي، والدعم الاجتماعي المدرك، وأنه يمكن التنبؤ بنمو ما بعد الصدمة من خلال كل من الذكاء الروحي والدعم الاجتماعي المدرك.Abstract: This study aims at identifying both of spiritual intelligence, perceived social support and post-traumatic growth at a sample of cancer patients, and to unveil the relationship of posttraumatic growth with the spiritual intelligence and perceived social support. This study is conducted on a sample of )53( cancer patients of both sexes who were chosen intentionally from Ibn Sina Hospital of Oum El Bouaghi. The searcher used the spiritual intelligence scale prepared by her, perceived social support prepared by Tachtoche (2015), post-traumatic growth prepared by Kaabar (2017). The statistic treatment of data revealed that the members of the cancer patients sample have high levels of spiritual intelligence, perceived social support and post-traumatic growth. The study results revealed also the existence of a positive statistically significant correlation relation at the indication level of (0.01) between the post-traumatic growth and both of the spiritual intelligence and perceived social support. One can predict the post-traumatic growth through the spiritual intelligence and religious commitment.
مقال
Keywords: الدعم الاجتماعي المدرك ; الذكاء الرحي ; ما بعد الصدمة ; نم ; منبئات ; مرضى السرطان; Spiritual intelligence; Perceived social support; Post-traumatic growth; Predictors; cancer